Vascularized fibular grafting following tumor resection demonstrates acceptable long-term outcomes in Denmark: a national retrospective cohort study - Christian Lind Nielsen; Daniel Thor Halberg Dybdal; Peter Vester-Glowinski; Lisa Lyngsie Hjalgrim; Pernille Edslev Wendtland; Birgitte Jul Kiil; Michael Melchior Bendtsen; Michael Mørk Petersen; Thomas Baad-Hansen (Acta Orthopaedica)
Background and purpose: Vascularized fibular grafting following tumor resection is an essential treatment option in limb salvage surgery. We aimed to evaluate: (I) bone healing, (II) complications and reoperations, (III) limb salvage, and (IV) survival. Methods: We present a retrospective evaluation of a national cohort comprising 27 patients. The indications were 13 cases of Ewing sarcoma, 12 cases of osteosarcoma, and 2 cases of giant cell tumor. The median age at surgery was 16 years (interquartile range [IQR] 10–18), and the median follow-up was 82 months (IQR 32–101). Patients were analyzed overall, as well as in subgroups based on tumor location (upper versus lower extremity) and pathology (osteosarcoma versus Ewing sarcoma). Results: The primary rate of graft union was 63%, and after secondary procedures the overall rate of graft union was 67%, with a median time to union of 13 months (IQR 9–17). The reoperation rate was 74%, while the limb salvage rate was 93%. The 5-year overall survival rate was 81% (95% confidence interval [CI] 61–92). Patients with upper extremity tumors were more likely to attain graft union (risk ratio [RR] 5.5, CI 1.3–31.5) and less likely to undergo multiple reoperations (RR 0.3, CI 0.8–0.9) than patients with lower extremity tumors. Conclusion: Vascularized fibular grafting following tumor resection was associated with a graft union rate of 67%, a high frequency of reoperations, a high limb salvage rate (93%), and a 5-year survival rate of 81%.